Northern Negros Aquatic resource Management Advisory Council as a Co-Management Strategy in Coastal resource Management. - Reyes, Remoleza (Miagao, Iloilo, Phils. University of the Philippines Visayas, 2006)
9This study was conducted to determine the effectiveness of Northern Negros Aquatic Resource Management Advisory Council (NNARMAC) base on the council's performance vis- a vis co-management indicators and the factors affecting its effectiveness through the Key Informant Interviews (KII) and Focus Group Discussions (FGD).The respondents were 5 mayors; 7 Sanggunianng Pambansa/ Sangguniang Bayan Members, chairman of the committee on Agriculture & Fisheries; 8 Municipal/ City Agriculturist; 5 fishery technician, 46 fisherfolks, and 2 NGOs. Based on the KII results, out of 13 modified co-management indicators only four were present in the area. Hence, factors affecting its effectiveness were identified. Grassroots level, NGOs, and POs were disregarded in their demands as they advocate for the delegation or sharing of power from the local government units to the community to manage the local fisheries resources. NNARMAC LGU ignored it. The relationship of co-management effort between the local government units and the community was not attined. In thet level, the government has not taken off from the process of delegating the power and sharing of authority in managing the coastal resources. massive IEC campaigns to all coastal baranagays of each LGU member must be done so that they will join efforts with the council in the implementation of coastal resource management program and projects. Some strategies in actualizing these are series of orientations, consultations, and workshops on coastal management.
Special Problem (MMA) -- Miagao, Iloilo : U.P. Visayas, 2006.
Keywords: Aquatic management